THE VULNERABILITY OF NOVICE EFL TEACHERS IN FORMAL AND NON-FORMAL TEACHING ENVIRONMENT - Erina Andriani; Concilianus Laos Mbato (IJEE (Indonesian Journal of English Education), 2022)
ABSTRACTStudies have investigated teacher vulnerability and its relation to teacher identity construction. Teacher vulnerability may emerge from internal and external conflicts based on teachers’ experiences. Though studies covered internal and external challenges for teachers, they rarely compared the academic environment aspect. This research intended to see if environment variables as external factors caused different experiences and vulnerabilities in novice EFL teachers. Therefore, this research aimed to determine if the different academic environments in formal and non-formal settings posed distinct challenges for novice EFL teachers. This study used narrative inquiry with a reflection and interview to gather the data. The participants were four novice EFL teachers: two teachers from formal education (FE) and non-formal education (NFE). The results showed that FE and NFE teachers shared some challenges, including student participation and classroom management, that led to vulnerability. Still, FE and NFE teachers also shared their distinct challenges. The teachers had similar strategies to cope with their vulnerability, but FE and NFE teachers employed additional strategies to face their distinct challenges. This study may help teachers consider different teaching environments for identifying and overcoming vulnerability. ABSTRAKBanyak studi telah meneliti kerentanan guru dan relasinya dengan pembentukan identitas guru. Kerentanan guru dapat tumbuh dari pertentangan internal dan eksternal, berdasarkan pengalaman para guru. Walau banyak studi telah mempelajari tantangan internal dan ekternal guru, namun belum banyak studi yang membandingkan aspek lingkungan akademik. Penelitian ini bertujuan untuk melihat apakah variabel lingkungan sebagai faktor eksternal menyebabkan perbedaan pengalaman dan kerentanan bagi guru Bahasa Inggris pemula. Maka dari itu, penelitian ini bertujuan untuk melihat apakah lingkungan akademik formal dan non-formal yang berbeda memberikan tantangan yang berbeda bagi guru Bahasa Inggris pemula. Penelitian ini menggunakan penelitian naratif dengan refleksi dan wawancara untuk mengumpulkan data. Responden studi ini adalah empat guru Bahasa Inggris pemula, dua orang dari pendidikan formal (PF) dan dua orang dari pendidikan non-formal (PNF). Hasil penelitian menunjukkan bahwa guru pendidikan formal dan non-formal mengalami berbagai tantangan serupa, seperti partisipasi siswa dan manajemen kelas, yang merujuk pada kerentanan guru, namun guru PF dan PNF juga mengalami tantangan yang berbeda. Untuk mengatasi kerentanan mereka, guru juga menerapkan strategi yang serupa, namun guru PF dan PNF juga menerapkan beberapa strategi yang berbeda dalam mengatasi tantangan. Penelitian ini dapat membantu para guru untuk mempertimbangkan lingkungan mengajar yang berbeda dalam mengidentifikasi dan mengatasi kerentanan.